RINDIK VOICE SYNTHESIS USING MODIFIED FREQUENCY MODULATION AS BALI CULTURAL PRESERVATION EFFORTS - I Made Widiartha; Agus Muliantara (Jurnal Ilmiah Kursor, 2016)
Gamelan bali is one aspect of the art highly favored by both domestik and foreign tourists. One type of popular typical Balinese gamelan is Rindik. Rindik is one of Balinese traditional musical instrument made of bamboo. Now days, the number of foreign culture and today’s lifestyle give some impacts on the declining interest of Balinese to interact with this type of conventional gamelan. The younger generation is now more inclined to like devices which are played through electronics/software component. To increase public interest towards traditional gamelan bali especially rindik we need a breakthrough to digitize gamelan rindik and presenting it in the form of rindik software application. Today's advanced technology has made a way to digitize a wide range of instruments including rindik into computerized form. For example we can use frequency modulation as a voice synthesis technique. This method was developed by researchers in the field of sound synthesis. In this research, we have done the sound synthesis process of rindik instrument into digital form using frequency modulation. The best results were obtained through the synthesis comparison of carrier signal frequency and modulator is 1:7. Outcomes of this research is a digitizing result which is presented in the form of a gamelan rindik package on desktop based software application.